2021
DOI: 10.1080/2331186x.2021.1940635
|View full text |Cite
|
Sign up to set email alerts
|

Context-based teaching and learning practices in upper primary science classrooms in East Gojjam administrative Zone, Ethiopia

Abstract: The main purpose of this study was to examine teachers' self-perceived practices of context-based science teaching and learning in science classrooms. To achieve this purpose, a cross-sectional survey design was employed. The data were collected from 360 upper primary science teachers in East Gojjam Administrative Zone, Ethiopia. A multistage sampling technique was employed to select the participants. A Context-Based Learning Environment in Science (CBLES) instrument was adapted and validated to measure teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…As Joshi and Verspoor (2013) mentioned, among other pressing problems, the overloaded curriculum nature in Ethiopia is accounted for the implementation of unsuccessful instruction, which is also one of the consequences for student's poor performance in reasoning. In Ethiopian context, the effort to make learning context-based is minimal (Gebeyaw et al, 2021) and, as a result, students find no meaning or relevance in what they learn. Scholars suggest that science learning, in whatever method delivered, should be context-and culture-based (Bennett et al, 2006;Gilbert et al, 2011).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…As Joshi and Verspoor (2013) mentioned, among other pressing problems, the overloaded curriculum nature in Ethiopia is accounted for the implementation of unsuccessful instruction, which is also one of the consequences for student's poor performance in reasoning. In Ethiopian context, the effort to make learning context-based is minimal (Gebeyaw et al, 2021) and, as a result, students find no meaning or relevance in what they learn. Scholars suggest that science learning, in whatever method delivered, should be context-and culture-based (Bennett et al, 2006;Gilbert et al, 2011).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…This might be due to the fact that teachers might not be competent enough to address context-based teaching learning in the classrooms. Teshager et al (2021) revealed that science teachers in Ethiopia could not lead children's context-based inquiries; besides, they failed to understand how knowledge in science evolves (i.e., with uncertainty) and is subjected to cultural and societal influences. Teachers themselves are unwilling to incorporate curriculum relevance into their research, and they place unreasonably high expectations on their students to exhibit certain traits and behaviors in their instruction (Meskerem, 2017).…”
Section: Introductionmentioning
confidence: 99%